A method for producing tantalum powder and tantalum powder obtained by the method
Patent Information
- Application Number
- CN202480002575.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing methods for preparing tantalum powder suffer from problems such as complex production processes, long processing cycles, low yields, and high costs, making it difficult to meet the requirements of high-reliability capacitors.
The microstructure of tantalum powder is optimized by using metallic magnesium to perform oxygen de-oxidation activation treatment on tantalum powder in a hydrogen-containing atmosphere, followed by sintering in the molten salt, separation of excess metallic magnesium, and protection with inert gas.
This improved the yield and withstand voltage of tantalum powder while reducing production costs, and enhanced the specific capacitance and breakdown voltage performance of capacitors under high-voltage conditions.
Smart Images

Figure CN119730980B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of rare metal functional material smelting, specifically relating to tantalum powder for making high-reliability capacitors and its manufacturing method. Background Technology
[0002] Tantalum electrolytic capacitors (hereinafter referred to as tantalum capacitors) have advantages such as high capacitance, small size, strong self-healing ability, and high reliability, and are widely used in high-end technology fields such as communications, computers, automotive electronics, medical devices, radar, aerospace, and automatic control devices. Tantalum powder is the key material for making tantalum capacitors. Only by using capacitor-grade tantalum powder with excellent voltage resistance can reliable tantalum capacitors be produced, thus continuously meeting the high reliability requirements of electronic devices and electronic circuits.
[0003] Currently, the main industrial methods for preparing capacitor-grade tantalum powder include sodium reduction of potassium fluorotantalate, magnesium reduction of tantalum oxide, and tantalum ingot hydrogenation. Regardless of the method used, to improve the electrical properties of tantalum powder, subsequent treatments such as high-temperature, high-vacuum heat treatment and magnesium reduction to reduce oxygen are necessary. High-temperature, high-vacuum heat treatment removes gaseous impurities and some low-melting-point metallic impurities, while magnesium reduction lowers the oxygen content and improves oxygen distribution within the powder. Furthermore, these subsequent treatments allow tantalum particles to agglomerate and sinter, improving the particle structure and enhancing the electrical properties of the tantalum powder. To improve the withstand voltage of tantalum powder, common practices include increasing the sintering temperature and extending the sintering time. However, increasing the sintering temperature and extending the sintering time can lead to a loss of specific capacitance.
[0004] CN114210973B discloses a sintering method that improves the voltage resistance of tantalum powder while maintaining a high specific volume. The method involves using metallic magnesium to deoxidize and activate the tantalum powder in a molten salt solution, then separating the excess magnesium, sintering the tantalum powder in the molten salt, further purifying the tantalum powder with water and acid, followed by high-temperature, high-vacuum heat treatment, magnesium reduction for deoxidation, and acid washing to obtain tantalum powder with improved high-voltage electrical properties. However, this molten salt-assisted heat treatment method suffers from low yield and a relatively complex process.
[0005] However, the above-mentioned molten salt-assisted heat treatment method for preparing tantalum powder has problems such as a relatively complex production process, a long process cycle, low yield, and high production cost. Summary of the Invention
[0006] The purpose of this invention is to provide a tantalum powder for capacitors with high breakdown voltage that meets the requirements for manufacturing high-reliability capacitors. Another purpose is to provide a method for preparing tantalum powder that can improve the yield of tantalum powder. The method is characterized by using metallic magnesium in a hydrogen-containing atmosphere to perform oxygen de-oxidation activation treatment on tantalum powder in molten salt, while simultaneously sintering the tantalum powder in molten salt, and then separating the excess metallic magnesium.
[0007] The purpose of this invention is to provide a method for producing tantalum powder for capacitors. The tantalum powder for capacitors produced by this method has a specific capacitance that is comparable to or higher than that of tantalum powder for capacitors of the same grade produced by the prior art under high voltage conditions, and a breakdown voltage that is comparable to or higher. This method can significantly improve the withstand voltage performance of tantalum powder for capacitors. More importantly and more preferably, while satisfying these advantageous properties, it can also increase the yield of tantalum powder and reduce the production cost of tantalum powder.
[0008] This invention relates to a method for producing tantalum powder, comprising the following steps:
[0009] (1) Mix tantalum powder raw material with excess metallic magnesium and at least one halide selected from alkali metals and / or alkaline earth metals evenly, put it into a sealed reaction container, remove the air from the container, and place the container in a heating furnace.
[0010] (2) Raise the temperature of the heating furnace to 700~1000℃ and keep it at that temperature for, for example, for 4h~20h, so that the oxygen in the tantalum powder reacts with magnesium in the molten salt and sintering is achieved at the same time;
[0011] (3) After the heat preservation is completed, the temperature of the heating furnace is kept at 600~750℃. The furnace is evacuated, for example, evacuated to below 10Pa, for example, below 5Pa. The furnace is then kept under negative pressure for 3h~10h to separate the excess magnesium metal from the tantalum powder mixture.
[0012] (4) Then, inert gas is introduced into the reaction vessel to maintain positive pressure. The reaction vessel is then cooled to room temperature and passivated to obtain a mixture containing halides and tantalum powder.
[0013] (5) Separate tantalum powder from the obtained mixture, for example by washing with water, acid washing, filtration, and drying.
[0014] In step (1), after the air is evacuated, the container is filled with hydrogen-containing gas, for example by introducing hydrogen-containing gas or by adding a hydrogen-containing substance and causing it to release hydrogen gas. Preferably, the hydrogen-containing substance is separated from other raw materials such as tantalum oxide powder, magnesium metal, alkali metal and / or alkaline earth metal halides, which can be achieved, for example, by placing the hydrogen-containing substance separately in a crucible.
[0015] Preferably, the hydrogen-containing material is, for example, hydrogen-adsorbed tantalum powder (also known as hydrogen-containing tantalum powder or hydrogen-containing tantalum powder), hydrogen-containing niobium powder, hydrogen-containing titanium powder, and hydrogen-containing compounds, which can release hydrogen gas at high temperatures. To simplify the process and improve purity, hydrogen-containing tantalum powder is preferred.
[0016] Preferably, the mass ratio of tantalum powder to alkali metal and / or alkaline earth metal halide in step (1) is 1:0.15~10.0, more preferably 1:0.15~3.0. The amount of excess magnesium refers to the amount of magnesium required to completely convert the oxygen in the tantalum powder into magnesium oxide, calculated based on the reaction equation Ta₂O₅ + 5Mg = 2Ta + 5MgO. The inventors have found that when the amount of magnesium used is more than 1.5 times the theoretical amount calculated using this reaction equation, a better effect is achieved. In this invention, "excess magnesium" refers to more than the theoretical amount, preferably more than 1.5 times, for example more than 3.5 times, preferably 5-12 times, more preferably 7-10 times, and even more preferably 4-7 times.
[0017] Preferably, the magnesium in step (1) is magnesium particles, more preferably magnesium particles with a purity of 3N5 or higher (i.e., 99.95% purity), and the lower the metallic impurities in the magnesium particles, the better. There is no limitation on the particle size of the magnesium particles. However, the inventors have found through extensive research that magnesium particles with a particle size of 150-4000 μm are more suitable for this technology. Magnesium particles in this particle size range not only facilitate the safe storage and transportation of metallic magnesium but also promote uniform mixing. If the magnesium particles are too fine, they are too reactive and prone to spontaneous combustion; if the magnesium particles are too coarse, they are not conducive to uniform mixing and optimization of tantalum powder performance.
[0018] Preferably, the alkali metal or alkaline earth metal halide in step (1) is one or more mixed salts of NaCl, KCl, KF, KI, and / or MgCl2. The alkali metal halide can be sodium chloride and / or potassium chloride. Preferably, it is a mixture of sodium chloride and potassium chloride; more preferably, the ratio of sodium chloride to potassium chloride in the mixture is 1:1-10; most preferably, it is about 1:1. The alkali metal or alkaline earth halide is preferably of analytical grade, and preferably of higher purity. The alkali metal and / or alkaline earth metal chloride is preferably in particulate form. There is no limitation on the particle size, but the inventors have found that particles of 70 μm-4000 μm are more suitable for this technology, resulting in tantalum powder with better pressure resistance.
[0019] Preferably, in step (1), one or more compounds containing elements B, P, and / or N may be added as additives to dope the tantalum powder. Based on the amount of effective elements, the amount of B added is preferably 1-100 ppm, more preferably 20-60 ppm; the amount of P added is preferably 10-200 ppm, more preferably 30-90 ppm; and the amount of N added is preferably 300-2500 ppm, more preferably 500-1200 ppm. It should be understood that although compounds are added here, the effective elements are B, P, and / or N, so the amounts mentioned here are calculated based on the amounts of B, P, and / or N.
[0020] The hydrogen-containing gas mentioned in step (1) is pure hydrogen or a mixture of hydrogen and an inert gas. The hydrogen can be gaseous hydrogen or hydrogen released from other hydrogen-containing substances. Preferably, the gas pressure inside the reaction vessel is positive. The partial pressure of hydrogen in the vessel is preferably greater than 0.050 kPa, preferably 0.1-200 kPa, more preferably 0.3-50 kPa, more preferably 70-100 kPa, more preferably 1-20 kPa, even more preferably 2-10 kPa or 10-15 kPa, and even more preferably 0.1-1.0 kPa. Too low a partial pressure of hydrogen cannot effectively promote the sintering effect, so the partial pressure of hydrogen is preferably not too low. Conversely, after the partial pressure of hydrogen is increased to a certain extent, the ability to improve the effect weakens, and from the perspective of ensuring the absolute safety of hydrogen, it is preferable to avoid choosing too high a partial pressure of hydrogen.
[0021] Inert gases generally refer to rare gases, such as helium, neon, and argon. Although nitrogen is sometimes considered an inert gas due to its stable properties, it is generally considered unsuitable as an inert protective gas in this field because the temperature in step 2) is relatively high, at which point nitrogen is highly reactive. However, after extensive research, the inventors unexpectedly discovered that the presence of a small amount of nitrogen in the aforementioned inert gases does not compromise the inert protective atmosphere and can also incidentally achieve nitrogen doping of tantalum powder. From the perspective of achieving better nitrogen doping effect of tantalum powder, in step (1), when a mixture of inert gas and hydrogen-containing gas (such as pure hydrogen) is introduced, it is preferable to include 0.5-10% nitrogen, based on the total amount of hydrogen-containing gas and inert gas.
[0022] Preferably, in step (2), the heating furnace is heated to 750~1000℃. More preferably, the temperature is raised to 850~1000℃, and the holding time is 4h~20h, preferably 10-20h.
[0023] Preferably, in step (3), the furnace temperature is raised to 600-750°C. More preferably, to 620-660°C. Preferably, the furnace is evacuated to 5 Pa in this step, more preferably below 0.5 Pa. The holding time is not strictly limited, as long as it is sufficient to fully separate the excess magnesium and tantalum powder mixture. It should be understood that if the total amount of the mixture increases, the holding time should be extended accordingly.
[0024] The hydrogen-containing gas in step (1) can be a mixture of hydrogen and an inert gas. In this case, the inert gas in step (1) and step (4) can be the same or different. Preferably, in step (1) and / or (4), a positive pressure is maintained in the reactor.
[0025] Preferably, the method of the present invention further includes subsequent treatments such as high-temperature high-vacuum heat treatment, oxygen reduction, and acid pickling after step (5) to obtain tantalum powder suitable for manufacturing high-reliability tantalum capacitors. These treatments are all known processes in the prior art. In other words, these treatments can adopt any process known in the prior art. For example, the high-temperature high-vacuum heat treatment and passivation here can adopt the methods provided by patents CN201110039272.9, CN201120077798.1, CN201120077680.9, CN201120077305.4, etc., the oxygen reduction can adopt the methods provided by patents CN201420777210.7, CN201420777210.7, and the acid pickling can adopt the methods provided by patents CN201210548101.3, CN201280077499.5, CN201210548008.2, etc.
[0026] As an alternative to incorporating N, P, and / or B elements in step (1), the present invention may also include a separate step of incorporating these elements, for example, after step (5). Of course, raw materials containing these elements can also be used directly. These elements can also be added during the aforementioned high-temperature, high-vacuum heat treatment steps. Incorporating P is particularly preferred. Adding P can increase the specific volume; as long as the total amount of P is controlled, the effect of increasing the specific volume is the same regardless of when it is added.
[0027] The present invention also relates to a tantalum powder suitable for manufacturing high-reliability tantalum capacitors and an anode block obtained from the tantalum powder, characterized in that the anode block made using the tantalum powder has a higher specific capacitance and a higher breakdown voltage in the breakdown voltage test when tested under high voltage energizing conditions.
[0028] This invention does not limit the raw material of tantalum powder to be processed. It can be tantalum powder obtained by magnesium reduction of tantalum oxide, tantalum powder obtained by sodium reduction of potassium fluorotantalate, or tantalum powder obtained by other reduction processes. It can be tantalum powder processed into flakes by physical methods, or tantalum powder obtained by hydrogenation and crushing of metallic tantalum. Although these tantalum powders inevitably contain a certain amount of oxygen, this invention does not have special requirements for the oxygen content. There are also no requirements for the specific surface area of the tantalum powder. However, the inventors have found that tantalum powder obtained by magnesium reduction of tantalum oxide is superior.
[0029] Moreover, the process of this invention is simple and easy to control. For example, microwaves and excessively high temperatures are not used in any of the steps of this invention. Therefore, the equipment used is also relatively simple, and the tantalum powder sintering process is safer.
[0030] Although hydrogen cannot reduce tantalum oxide, it plays an important role in this invention. Without being bound by general theory, and combining the analysis principle of powder-liquid phase sintering theory, the inventors believe that the excellent effect of this invention is due to the following: In step (2), as the temperature increases, magnesium and alkali or alkaline earth metal chlorides melt and appear as a liquid phase. In the presence of hydrogen gas in the atmosphere, the hydrogen gas promotes the diffusion of oxygen content from the tantalum powder surface to the liquid magnesium, making reduction easier and increasing the surface activity of the tantalum powder particles. In the molten magnesium and alkali or alkaline earth metal chlorides, the sharp edges, micro-protrusions, and ultrafine tantalum powder particles of large particles dissolve in the liquid phase. As the process continues, when the concentration of tantalum in the liquid phase exceeds the saturation concentration, it will preferentially deposit in certain parts of the large tantalum particles and combine into part of the large particles. At the same time, in the presence of hydrogen, it can promote further sintering between tantalum powder particles, thus making the particles smooth, the sintering neck large, and the ultrafine particles few. Due to the relatively low melting point of tantalum metal (around 3000℃), this process allows for the sintering of tantalum powder into a microstructure suitable for manufacturing tantalum electrolytic capacitors. Simultaneously, the effective surface area of the tantalum powder used in capacitors is reduced less, which helps maintain the specific capacitance of the tantalum powder for capacitors. Subsequently, the obtained tantalum powder is subjected to high-temperature, high-vacuum sintering, oxygen reduction, and acid washing using existing techniques, resulting in tantalum powder suitable for manufacturing high-voltage, high-reliability capacitors.
[0031] If the tantalum powder, which is the product of the method of the present invention, is sintered into an anode block, it has an improved microstructure, specifically, the absence of ultrafine pores in the resulting anode block. These ultrafine pores are detrimental to electrical performance, particularly leakage current and ESR (equivalent series resistance). Attached Figure Description
[0032] The following figures are provided to better understand the invention. These figures are exemplary and are not intended to limit the scope of the invention.
[0033] Figure 1Scanning electron microscope images of tantalum powder obtained according to the present invention are given.
[0034] The attached figure illustrates that the obtained tantalum powder has a more uniform distribution, with smooth particles, large sintering necks, and fewer ultrafine particles. Detailed Implementation
[0035] To further illustrate the present invention, preferred embodiments are described below with reference to examples, which clearly demonstrate the purpose, features, and advantages of the present invention. However, these descriptions are merely for further illustrating the features and advantages of the present invention and are not intended to limit the invention. Unless otherwise specified in the examples, conventional conditions were followed. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0036] For the purposes of this specification, all figures indicating amounts of ingredients, reaction conditions, etc., in the specification and claims shall in all cases be understood to be modified by the term "about," unless otherwise specified. Accordingly, the numerical parameters given in the following specification and appended claims are approximate values, which may vary according to the desired properties sought to be obtained according to the invention, unless indicated to the contrary. At least, and without limitation, the application of the doctrine of equivalence to the scope of the claims is intended, each numerical parameter shall be interpreted at least according to the number of significant figures reported and in accordance with ordinary rounding techniques.
[0037] The analysis of impurity content in tantalum powder was conducted according to Chinese standards GB / T15076.1~15076.15, and the physical properties were performed according to industry standard YS / T573-2015. The testing of electrical properties in tantalum powder was conducted according to Chinese standard GB / T3137.
[0038] Example 1
[0039] Tantalum powder was obtained by reducing tantalum oxide with 5.0 kg of magnesium. 2.6% (4.95 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) and 3.75 kg of potassium chloride (KCl) were added. After thorough mixing, the mixture was placed in a sealed reaction vessel, and the air inside the vessel was evacuated. A mixture of hydrogen and argon was introduced into the reaction vessel, maintaining a hydrogen partial pressure of 20 kPa. Under positive pressure, the reaction vessel was placed in a furnace and heated to 930°C, held for 15.0 hours, and then the temperature was lowered to 640°C for evacuation. The pressure inside the reaction vessel was reduced to 5.7 Pa, held for 5 hours, and then evacuation was stopped. Argon was then introduced into the reaction vessel to maintain positive pressure, and the mixture was cooled to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.63 kg of tantalum powder. The tantalum powder yield was calculated, and the Fsss particle size of the tantalum powder was analyzed. The results are listed in Table 1.
[0040] The obtained tantalum powder was added to 50 ppm phosphorus and subjected to a reaction at 1400°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 200V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0041] Comparative Example 1
[0042] Tantalum powder was obtained by reducing tantalum oxide with 5.0 kg of magnesium. 2.6% (4.95 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) and 3.75 kg of potassium chloride (KCl) were added, mixed thoroughly, and then placed into a reaction vessel. The air in the reaction vessel was evacuated. Argon gas was introduced into the reaction vessel, and under positive pressure, the vessel was placed in a furnace and heated to 930°C, held for 15.0 hours, then the temperature was lowered to 640°C and evacuated to reduce the pressure to 5.7 Pa. The pressure was then maintained at 5.7 Pa for 5 hours, and evacuation was stopped. Argon gas was then introduced into the reaction vessel again to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.12 kg of tantalum powder. The tantalum powder yield was calculated, and the Fsss particle size of the tantalum powder was analyzed. The results are listed in Table 1.
[0043] The obtained tantalum powder was added to 50 ppm phosphorus and subjected to a reaction at 1400°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 200V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0044] Example 2
[0045] 5.0 kg of magnesium was used to reduce tantalum oxide to obtain tantalum powder. 3.3% (6.98 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) was added, along with 1.0 kg of potassium chloride (KCl) and 1.0 kg of sodium chloride (NaCl). After thorough mixing, the mixture was placed in a reaction vessel, and the air inside the vessel was evacuated. A mixture of hydrogen and argon was introduced into the reaction vessel, controlling the hydrogen partial pressure to 0.350 kPa. Under positive pressure, the reaction vessel was placed in a furnace and heated to 970°C, held for 20.0 hours, then the temperature was lowered to 680°C and evacuated to reduce the pressure inside the vessel to 5.7 Pa. This temperature was maintained for 8 hours before evacuation was stopped. Argon gas was then introduced into the reaction vessel to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.70 kg of tantalum powder. The yield of tantalum powder was calculated, and the Fsss particle size of tantalum powder was analyzed. The results are listed in Table 1.
[0046] The obtained tantalum powder was subjected to a temperature of 1450℃ and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 300V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0047] Comparative Example 2
[0048] Tantalum powder was obtained by reducing tantalum oxide with 5.0 kg of magnesium. 3.3% (6.98 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) was added, along with 1.0 kg of potassium chloride (KCl) and 1.0 kg of sodium chloride (NaCl). After thorough mixing, the mixture was placed in a reaction vessel, and the air inside the vessel was evacuated. Argon gas was introduced into the reaction vessel, and under positive pressure, the vessel was placed in a furnace and heated to 970°C for 20.0 hours. The temperature was then lowered to 680°C, and the vessel was evacuated to reduce the pressure to 5.7 Pa. The pressure was maintained at this temperature for 8 hours, and then evacuation was stopped. Argon gas was then introduced into the reaction vessel again, and under positive pressure, the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.04 kg of tantalum powder. The tantalum powder yield was calculated, and the Fsss particle size of the tantalum powder was analyzed. The results are listed in Table 1.
[0049] The obtained tantalum powder was subjected to a temperature of 1450℃ and a pressure below 5.0 × 10⁻⁶.-3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 300V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0050] Example 3
[0051] 5.0 kg of magnesium was used to reduce tantalum oxide to obtain tantalum powder. 7.3% (7.91 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) was added, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl). After thorough mixing, the mixture was placed in a reaction vessel, and the air inside the vessel was evacuated. A mixture of hydrogen and argon gas was introduced into the reaction vessel, maintaining a hydrogen partial pressure of 50 kPa. Under positive pressure, the reaction vessel was placed in a furnace and heated to 830°C, held for 12.0 hours, and then the temperature was lowered to 650°C for evacuation. The pressure inside the reaction vessel was reduced to 5.7 Pa, held for 8 hours, and then evacuation was stopped. Argon gas was then introduced into the reaction vessel to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.50 kg of tantalum powder. The yield of tantalum powder was calculated, and the Fsss particle size of tantalum powder was analyzed. The results are listed in Table 1.
[0052] The obtained tantalum powder was subjected to a temperature of 1250℃ and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 60V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0053] Comparative Example 3
[0054] Tantalum powder was obtained by reducing tantalum oxide with 5.0 kg of magnesium. 7.3% (7.91 times the theoretical amount) of metallic magnesium granules (based on the weight of the tantalum powder) was added, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl), and 50 ppm of phosphorus. The mixture was thoroughly mixed and then placed in a reaction vessel. Air was evacuated from the reaction vessel. Argon gas was introduced into the reaction vessel to maintain positive pressure. The vessel was then placed in a furnace and heated to 830°C, held for 12.0 hours, and then the temperature was lowered to 650°C for evacuation. The pressure in the reaction vessel was reduced to 5.7 Pa, held for 8 hours, and then evacuation was stopped. Argon gas was then introduced into the reaction vessel again to maintain positive pressure, and then the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 3.81 kg of tantalum powder. The tantalum powder yield was calculated, and the Fsss particle size of the tantalum powder was analyzed. The results are listed in Table 1.
[0055] The obtained tantalum powder was subjected to a temperature of 1250℃ and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The tantalum powder was then used to fabricate anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 60V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 2. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 2.
[0056] Table 1. Results of molten salt-assisted sintering yield and FSSS particle size test
[0057] Table 2 Electrical performance data of finished tantalum powder
[0058] Example 4
[0059] 5.0 kg of sodium was used to reduce potassium fluorotantalate to obtain tantalum powder. 5.0% (4.09 times the theoretical amount) of magnesium granules (based on the weight of the tantalum powder) was added, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl). The mixture was thoroughly mixed and placed into a reaction vessel. 800 g of tantalum metal containing 5237 ppm hydrogen was separately placed in a crucible and added to the same reaction vessel separately from the tantalum powder, thus removing air from the reaction vessel. Argon gas was introduced into the reaction vessel, which was then placed in a furnace for heating. During the heating process, the hydrogen-containing tantalum metal released hydrogen gas. The temperature was raised to 880°C and held for 10.0 hours. The temperature was then lowered to 640°C and evacuated to reduce the pressure in the reaction vessel to 5.7 Pa. This temperature was maintained for 10 hours before evacuation was stopped. After the heat preservation was completed, argon gas was introduced into the reaction vessel to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The tantalum metal that provides hydrogen was recovered separately. The resulting mixture of halide and tantalum powder was washed with water, acid washed, filtered, and dried to obtain 4.50 kg of tantalum powder. The yield of tantalum powder was calculated, and the Fsss particle size of tantalum powder was analyzed. The results are listed in Table 3.
[0060] The obtained tantalum powder was added to 90 ppm phosphorus and subjected to a reaction at 1240°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The anode block mass, pressing density, sintering temperature, and sintering time were specified in Table 4, and other conditions were in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder was then fabricated into anode blocks, energized at 60V, and the electrical performance was tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 4. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 4.
[0061] Comparative Example 4
[0062] 5.0 kg of sodium containing 800 ppm nitrogen was used to reduce potassium fluorotantalate to obtain tantalum powder. 5.0% (4.09 times the theoretical amount) of magnesium granules (based on the weight of the tantalum powder) was added, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl). The mixture was thoroughly mixed and placed in a reaction vessel, and the air in the reaction vessel was removed. Argon gas was introduced into the reaction vessel, which was then placed in a furnace and heated to 880°C for 10.0 hours. The temperature was then lowered to 640°C and evacuated to reduce the pressure in the reaction vessel to 5.7 Pa. This temperature was maintained for 10 hours, and then evacuation was stopped. After the evacuation, argon gas was introduced into the reaction vessel again to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The resulting mixture of halide and tantalum powder was washed with water, acid-washed, filtered, and dried to obtain 4.25 kg of tantalum powder. The tantalum powder yield was calculated, and the Fsss particle size of the tantalum powder was analyzed. The results are listed in Table 3.
[0063] The obtained tantalum powder was added to 90 ppm phosphorus and subjected to a reaction at 1240°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was obtained by high-temperature, high-vacuum heat treatment for 0.5 hours under Pa, followed by deoxygenation and acid washing. The anode block mass, pressing density, sintering temperature, and sintering time were specified in Table 4, and other conditions were in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder was then fabricated into anode blocks, energized at 60V, and the electrical performance was tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 4. In the specific capacitance test, the test was conducted using a 30% H2SO4 solution followed by a 10% H3PO4 solution. The results are listed in Table 4.
[0064] Example 5
[0065] Take 5.0 kg of flake tantalum powder containing 50 ppm boron compound, add 5.0% (6.12 times the theoretical amount) of magnesium granules by weight of tantalum powder, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl). Mix thoroughly and place into a reaction vessel. Separately place 800 g of tantalum metal containing 5237 ppm hydrogen in a crucible and add it separately from the tantalum powder into the same reaction vessel to remove air from the reaction vessel. Introduce argon gas into the reaction vessel and place it in a furnace for heating. During the heating process, the hydrogen-containing tantalum metal releases hydrogen gas. Heat to 920°C and hold for 10.0 hours. Then lower the temperature to 660°C and evacuate the vessel to reduce the pressure to 5.7 Pa. Hold for 10 hours and then stop evacuation. After the heat preservation was completed, argon gas was introduced into the reaction vessel to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The tantalum metal that provides hydrogen was recovered separately. The resulting mixture of halide and tantalum powder was washed with water, acid washed, filtered, and dried to obtain 4.70 kg of tantalum powder. The yield of tantalum powder was calculated, and the Fsss particle size of tantalum powder was analyzed. The results are listed in Table 3.
[0066] The obtained tantalum powder was added to 30 ppm phosphorus and subjected to a reaction at 1360°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was subjected to high-temperature, high-vacuum heat treatment for 0.5 hours at Pa, followed by deoxygenation and acid washing to obtain tantalum powder. The tantalum powder was fabricated into anode blocks according to the anode block mass, pressing density, sintering temperature, and sintering time specified in Table 4, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 150V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 4. In the specific capacitance test, the tantalum powder was tested first with 30% H2SO4 solution and then with 10% H3PO4 solution. The results are listed in Table 4.
[0067] Comparative Example 5
[0068] Take 5.0 kg of flake tantalum powder containing 50 ppm boron compound, add 5.0% (6.12 times the theoretical amount) of metallic magnesium granules by weight of tantalum powder, along with 2.0 kg of potassium chloride (KCl) and 2.0 kg of sodium chloride (NaCl), mix thoroughly, and then load into a reaction vessel. Separate the air from the reaction vessel. Introduce argon gas into the reaction vessel, place it in a furnace, heat to 920°C, and hold for 10.0 hours. Then, lower the temperature to 660°C and evacuate the vessel, reducing the pressure to 5.7 Pa. Hold for 10 hours and then stop evacuation. After holding at this temperature, introduce argon gas into the reaction vessel again to maintain positive pressure, and then cool to room temperature for passivation treatment. Wash, acid-wash, filter, and dry the resulting mixture of halide and tantalum powder to obtain 4.00 kg of tantalum powder with improved particle structure. Calculate the tantalum powder yield, analyze the Fsss particle size of the tantalum powder, and list the results in Table 3.
[0069] The obtained tantalum powder was added to 30 ppm phosphorus and subjected to a reaction at 1360°C and a pressure below 5.0 × 10⁻⁶. -3 The tantalum powder was subjected to high-temperature, high-vacuum heat treatment for 0.5 hours at Pa, followed by deoxygenation and acid washing to obtain tantalum powder. The tantalum powder was fabricated into anode blocks according to the anode block mass, pressing density, sintering temperature, and sintering time specified in Table 4, while other conditions were in accordance with the aforementioned GB / T3137 requirements. The anode blocks were then energized at 150V, and their electrical properties were tested according to the aforementioned GB / T3137 requirements. The results are listed in Table 4. In the specific capacitance test, the tantalum powder was tested first with 30% H2SO4 solution and then with 10% H3PO4 solution. The results are listed in Table 4.
[0070] Table 3. Results of molten salt-assisted sintering yield and FSSS particle size test
[0071] Table 4 Electrical performance data of finished tantalum powder
[0072] As can be seen from Tables 1 and 3, the present invention has the following advantages compared with the prior art:
[0073] The tantalum powder manufactured using the method of this invention exhibits a significantly higher tantalum powder yield during the molten salt-assisted heat treatment process, which undoubtedly saves production costs. Therefore, this invention offers a lower cost advantage in manufacturing tantalum powder for high-reliability tantalum capacitors.
[0074] Moreover, the larger particle size of tantalum powder Fsss is beneficial to improving the reliability of tantalum capacitors.
[0075] Tables 2 and 4 also show that, when the tantalum powder manufactured according to this invention is energized under high pressure and the electrical performance of the energized block is tested, its electrical performance is comparable to, or even better than, that of the prior art. Furthermore, it can be seen that the anode block made with the tantalum powder described in this invention exhibits smaller differences in specific capacity after energization when tested with different acid solutions. It is generally believed that phosphoric acid and sulfuric acid have different surface tensions, resulting in different abilities to penetrate the ultrafine pores in the anode block. Therefore, the difference in specific capacity reflects the presence of ultrafine pores in the anode block; that is, the greater the difference, the more ultrafine pores there are. Therefore, these two tables further corroborate that using the tantalum powder according to this invention can yield anode blocks with fewer ultrafine pores and a better microstructure.
[0076] As can also be seen from Tables 1 and 2, in this invention, when the preparation method of tantalum powder is the same, using tantalum powder with a larger surface area and higher oxygen content as raw material can ultimately yield tantalum powder with a higher specific volume.
Claims
1. A method for producing tantalum powder, comprising the following steps: (1) Mix tantalum powder raw material with metallic magnesium and at least one halide selected from alkali metals and / or alkaline earth metals evenly, put it into a sealed reaction container, remove the air from the container, and place the container in a heating furnace. (2) Raise the temperature of the heating furnace to 700~1000℃ and keep it at that temperature so that the oxygen in the raw material tantalum powder reacts with magnesium in the molten salt and sintering is achieved; (3) After the heat preservation is completed, the temperature is lowered to 600~750℃, the furnace is evacuated, and the furnace is kept warm under negative pressure to fully separate the excess magnesium metal and tantalum powder mixture. (4) Inert gas is introduced into the reaction vessel and then cooled to room temperature and passivated to obtain a mixture containing halides and tantalum powder; (5) Separate tantalum powder; in, In step (1), after the air is extracted, the container is filled with hydrogen gas. The tantalum powder raw materials are selected from tantalum powder obtained by magnesium reduction of tantalum oxide, tantalum powder obtained by sodium reduction of potassium fluorotantalate, tantalum powder processed into flakes by physical methods, or tantalum powder after hydrogenation and crushing of metallic tantalum.
2. The method according to claim 1, wherein after step (5), it further comprises the following step: (6) High-temperature and high-vacuum heat treatment; and (7) Separation.
3. The method according to claim 2, wherein separation is performed in step (7) by acid washing, filtration and drying.
4. The method according to claim 1, wherein in step (1) the container is made to contain hydrogen gas by adding a hydrogen-containing substance and causing it to release hydrogen gas.
5. The method according to claim 4, wherein the hydrogen-containing substance is tantalum metal with adsorbed hydrogen.
6. The method of claim 1, wherein the metallic magnesium is in the form of magnesium particles.
7. The method according to any one of claims 1-6, wherein in step (2), the temperature of the heating furnace is raised to 750~950°C.
8. The method according to any one of claims 1-6, wherein argon gas is introduced in step (2) and maintained at a positive pressure.
9. The method according to any one of claims 1-6, wherein in step (2), the temperature of the heating furnace is raised to 800-900°C.
10. The method according to any one of claims 1-6, wherein the heat preservation in step (2) is 4h to 20h.
11. The method according to any one of claims 1-6, wherein the heat preservation in step (2) is 10h to 20h.
12. The method according to any one of claims 1-6, wherein in step (3), the temperature is lowered to 620~680°C.
13. The method according to any one of claims 1-6, wherein in step (3), the vacuum level is reduced to below 10 Pa.
14. The method according to any one of claims 1-6, wherein in step (3), the pressure is evacuated to below 5 Pa.
15. The method according to any one of claims 1-6, wherein in step (3), the pressure is evacuated to below 0.5 Pa.
16. The method according to any one of claims 1-6, wherein the inert gas in step (4) is argon.
17. The method according to any one of claims 1-6, wherein the reaction vessel is kept under positive pressure in step (4).
18. The method according to any one of claims 1-6, wherein the separation in step (5) is carried out by washing, acid washing, filtering and drying the resulting mixture.
19. The method according to any one of claims 1-6, wherein in step (1) the container is made to contain hydrogen gas by introducing hydrogen gas.
20. The method according to any one of claims 1-6, wherein the mass ratio of tantalum powder to alkali metal and / or alkaline earth metal halide in step (1) is 1:0.15~10.
0.
21. The method according to claim 20, wherein the mass ratio is 1:0.15~3.
0.
22. The method according to claim 20, wherein the mass ratio is 1:1.5 to 2.
5.
23. The method according to any one of claims 1-6, wherein the magnesium metal in step (1) is in excess, and the amount of magnesium metal added is more than 1.5 times the theoretical amount of magnesium metal required to convert oxygen in tantalum powder into magnesium oxide.
24. The method according to claim 23, wherein the amount of magnesium metal added in step (1) is more than 3.5 times the theoretical amount of magnesium metal required to convert oxygen in tantalum powder into magnesium oxide.
25. The method according to claim 23, wherein the amount of metallic magnesium added in step (1) is 5-12 times the theoretical amount of metallic magnesium required to convert oxygen in tantalum powder into magnesium oxide.
26. The method according to claim 23, wherein the amount of magnesium added in step (1) is 7-10 times the theoretical amount of magnesium required to convert oxygen in tantalum powder into magnesium oxide.
27. The method according to claim 23, wherein the amount of magnesium metal added in step (1) is 4-7 times the theoretical amount of magnesium metal required to convert oxygen in tantalum powder into magnesium oxide.
28. The method according to any one of claims 1-6, wherein the alkali metal or alkaline earth metal halide in step (1) is one or a mixture of NaCl, KCl, KF, KI, and MgCl2.
29. The method according to any one of claims 1-6, wherein the alkali metal or alkaline earth metal halide in step (1) is a mixture of NaCl and KCl.
30. The method according to claim 29, wherein the mass ratio of NaCl to KCl in the mixture is 1:1-10.
31. The method according to claim 30, wherein the mass ratio of NaCl to KCl in the mixture is 1:
2.
32. The method of any one of claims 1-3, wherein in step (1) one or more compounds containing elements B, P and / or N are added as additives to dope the tantalum powder.
33. The method of claim 32, wherein The amount of element B added is 1-100 ppm, based on the amount of effective elements. And / or the added P element is 10-200 ppm; And / or the added nitrogen element is 300-2500 ppm.
34. The method of claim 33, wherein The amount of element B added is 20-60 ppm, based on the amount of effective elements. And / or the added P element is 30-90 ppm; And / or the added nitrogen element is 500-1200 ppm.
35. The method according to claim 8, wherein a mixture of argon and hydrogen is introduced in step (2), and the partial pressure of the hydrogen exceeds 0.050 kPa.
36. The method according to claim 8, wherein a mixture of argon and hydrogen is introduced in step (2), and the partial pressure of the hydrogen is 2.0-10 kPa.
37. The method according to claim 36, wherein the partial pressure of hydrogen in step (2) is 10-15 kPa.
38. The method according to claim 36, wherein the partial pressure of hydrogen in step (2) is 0.1-1.0 kPa.
39. The method according to claim 36, wherein the partial pressure of hydrogen in step (2) is 0.1-200 kPa.
40. The method according to claim 36, wherein the partial pressure of hydrogen in step (2) is 0.3-50 kPa.
41. The method according to claim 36, wherein the hydrogen partial pressure in step (2) is 50-100 kPa.
42. The method according to claim 36, wherein the partial pressure of hydrogen in step (2) is 1.0-20 kPa.
43. The method according to claim 36, wherein argon gas is introduced in both step (2) and step (4).
44. The method according to claim 36, wherein the inert gas introduced in step (4) is not argon.
45. Tantalum powder produced by the method according to any one of claims 1-44.
46. Use of tantalum powder in capacitors according to claim 45.
Citation Information
Patent Citations
Thermal treatment method of tantalum powder
CN102120258A
Stirring water-washing method and device for producing tantalum powder by reducing potassium fluotantalate via metallic sodium
CN102990076B
Method for purifying tantalum powder
CN102994780B
Method and apparatus for purifying target powder
CN105051223B
Tantalum metal surface inactivating equipment with argon forced cooling device
CN202072753U
